A Novel Approach to Fabricate a Polyamide-Copper TENG in Vertical Contact-Separation Mode - Sharma, Hitesh Kumar; Sharma, Atul Kumar; Janyani, Vijay; Boolchandani, Dharmendra (New Environmentally-Friendly Materials, 2025)
In this study, a novel design concept for a contact-separation Triboelectric Nanogenerator (TENG) utilizing polyimide (PI) film and copper (Cu) tape is presented. The innovation lies in enhancing the surface area and roughness of the PI film using 1000-grit sandpaper, which is manually rubbed over the film. This surface treatment significantly improves charge transfer between the PI and Cu layers, thereby enhancing the electrical performance of the TENG. The modified (rubbed) PI-Cu TENG achieved an open-circuit voltage (Voc) of 25 V and a short-circuit current (Isc) of 0.7 µA. Compared to a pristine (untreated) PI film, the hand-rubbed PI-Cu TENG demonstrated an increase in performance. Voc and Isc were improved by 78.6% and 75%, respectively, due to the increased surface roughness and area, which facilitated more efficient charge transfer at the interface. Additionally, the instantaneous power density showed a notable increase of 68.18% relative to the pristine film. The prototype device was characterized using a two-probe I-V measurement system to obtain Isc and Voc responses. Morphological changes in the rubbed PI film were confirmed via Scanning Electron Microscopy (SEM), performed using an FEI Nova Nano FESEM 450, revealing the presence of scratch-induced torsional layers. Surface roughness and topographical features were further analyzed using Bruker Multimode-8 Atomic Force Microscopy (AFM).